PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA (BEI) - Juniarmita, Andi Sartika; Haris, Andi Tenri Ellyana (Patria Artha Management Journal, 2021)
Working capital management is needed to find out the optimal amount of working capital needed by the company. The company's operational activities affect the income to be obtained by the company. The company's ability to generate profits over a certain period is called profitability. This can be used to assess the company's ability to use working capital effectively to generate a certain expected level of profit. As an investor, profitability is a benchmark for assessing the success of a company in running its business and can also be used as a benchmark in assessing the prospect of return from the capital to be invested. Manufacturing company is a company engaged in the manufacture of products. The urgency of this research is there as consideration for potential investors to invest in manufacturing companies listed on the BEI. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 periods, totaling 181 companies. The number of samples was determined using a purposive sampling method and focused on the consumer goods sector with a total of 30 companies. The data analysis technique used is multiple linear regressions. The results showed that cash turnover and inventory turnover had a positive and insignificant effect on profitability in manufacturing companies in the Consumer Goods Industry Sector. Accounts receivable turnover has a negative and insignificant effect on profitability in manufacturing companies in the Consumer Goods Industry Sector. Working capital management (cash turnover, accounts receivable and inventory) has a positive and insignificant effect on profitability in manufacturing companies